Investigation on pyrolysis of microalgae Botryococcus braunii and Hapalosiphon sp - Liu, Yong-Qiang (2013)
In this study, the thermochemical characteristics of two types of microalgae, namely Hapalosiphon sp. and Botryococcus braunii, were investigated by use of a thermogravimetric analyzer. The low calorific value of Hapalosiphon sp. was 14.75 MJ kg–1, which is close to that of sewage sludge or lignocellulosic biomass. However, the low calorific value of B. braunii was as high as 35.58 MJ kg–1 due to 89% of total C and H contents in biomass. Pyrolytic results indicated that the two microalgae had similar pyrolytic temperature ranges. In addition, with increased heating rates, the pyrolytic curves of the microalgae shifted to a higher temperature. However, derivative thermogravimetric (DTG) profiles of the two microalgae are distinct, which showed that different reactions were involved in the pyrolysis process. Hapalosiphon sp. has a lower mean activation energy than B. braunii in the pyrolysis process.